Therapeutic adherence in patients with diabetes mellitus type II and use of basic mobile technology: a systematic review - Martínez-Mateo, Minerva; García-Herrera, Daniel (Revista Española de Comunicación en Salud, 2019)
Objective: To review the scientific literature regarding the effectiveness of basic mobile technology in therapeutic adherence in patients diagnosed with diabetes mellitus type II (DMT2). Methodology: Quasi-systematic review, whose inclusion criteria were: 2.012-2.018, English and/ or Spanish, randomized and controlled clinical trials, subjects diagnosed with DMT2, basic mobile technology and results related to therapeutic adherence. The identified studies were evaluated by the Jadad’s scale. Results: Six studies were included: 4 used text messages and 2, phone calls. The duration of the intervention ranged from 3 to 18 months. 1.690 subjects diagnosed with DMT2 were recruited, of whom only 810 completed the studies. Limitations: Shortage of quality controlled and/or randomized clinical trials. There have been no studies that include the different components of therapeutic adherence in relation to the use of basic mobile technology. Conclusions: The use of basic mobile technology, together with health education, can improve the implication in the different components of therapeutic adherence in patients diagnosed with DMT2. Implications of the main findings: The use of basic mobile technology reinforces the concepts and the monitoring of people by health professionals.
Keywords: treatment adherence and compliance; text messaging; telephone; diet; exercise